2017
DOI: 10.1002/clc.22752
|View full text |Cite
|
Sign up to set email alerts
|

Decreased pulmonary arterial proportional pulse pressure is associated with increased mortality in group 1 pulmonary hypertension

Abstract: Background This study evaluated the utility of a novel index, pulmonary arterial (PA) proportional pulse pressure (PAPP; range 0–1, defined as [PA systolic pressure – PA diastolic pressure] / PA systolic pressure), in predicting mortality in patients with World Health Organization group 1 pulmonary hypertension (PH). Hypothesis Low PAPP is associated with increased 5‐year mortality independent of a validated contemporary risk‐prediction equation (Pulmonary Hypertension Connection [PHC] equation). Methods In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Consistent with this, we found that ARVC HT patients had a median age of 48 years, and compared with non-ARVC HT transplants, they had fewer co-morbidities (significantly less diabetes and tobacco use) and were more likely to have implantable cardioverter defibrillators. Reflective of their intrinsic RV-dominant pathology, ARVC patients in this study had significantly lower PA pressures compared with non-ARVC patients while having significantly narrower PA pulse pressures (an indirect measure of the combined effects of RV contractility and pulmonary vascular distensibility 29 ) and significantly impaired cardiac output, likely driving need for HT. Likewise, we have demonstrated that patients with ARVC can have impaired ventilatory efficiency, which is in turn associated with HF and need for HT.…”
Section: Discussionmentioning
confidence: 82%
“…Consistent with this, we found that ARVC HT patients had a median age of 48 years, and compared with non-ARVC HT transplants, they had fewer co-morbidities (significantly less diabetes and tobacco use) and were more likely to have implantable cardioverter defibrillators. Reflective of their intrinsic RV-dominant pathology, ARVC patients in this study had significantly lower PA pressures compared with non-ARVC patients while having significantly narrower PA pulse pressures (an indirect measure of the combined effects of RV contractility and pulmonary vascular distensibility 29 ) and significantly impaired cardiac output, likely driving need for HT. Likewise, we have demonstrated that patients with ARVC can have impaired ventilatory efficiency, which is in turn associated with HF and need for HT.…”
Section: Discussionmentioning
confidence: 82%
“…(19)(20)(21)(22) A recent iteration utilized the PAPP indexed to systolic pulmonary artery pressure (SPAP) with higher values predicting more favorable outcomes in pulmonary arterial hypertension cohorts. (23) The role of PAPP or PAPP indices as indicators of RV function remain undefined in ECMO.…”
Section: Abbreviationsmentioning
confidence: 99%
“…[20][21][22][23] A recent iteration utilized the PAPP indexed to systolic pulmonary artery pressure (SPAP) with higher values predicting more favorable outcomes in pulmonary arterial hypertension cohorts. 24 The role of PAPP or PAPP indices as indicators of right heart function remains undefined in ECMO.…”
mentioning
confidence: 99%